Association of Serum C-Peptide with the Components of Metabolic Syndrome among Non Diabetic Obese (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Obesity is a major health concern and is associated with metabolic syndrome that increases the risk for cardiovascular disease and diabetes mellitus. C-peptide or connecting peptide, is a short polypeptide that connects A-chain of insulin to its B-chain in the proinsulin molecule.  In different studies it was found that C-peptide level are associated with Metabolic Syndrome and its complication. C-peptide is also reported to be more reliable than insulin as a measure of endogenous insulin secretion, insulin resistance and pancreatic beta cell function. The aim of the study is to observe the association of C-peptide levels with the components of metabolic syndrome in non diabetic obese subjects.Materials and methods: This was a hospital based cross- sectional study comprising hundred non diabetic apparently healthy obese subjects age between 30-70 years. This study was carried out at the Department of Biochemistry and Outpatient Department of endocrinology, Chittagong Medical College Hospital. Samples were collected by non-probability convenient sampling.  Results: Serum C-peptide was significantly higher in Metabolic Syndrome positive subjects (4.29 ±0.28 ng/ml) than non-Metabolic Syndrome (1.72 ± 0.12ng/ml). There was significant association between Metabolic Syndrome and increased serum C-peptide concentration. Serum Cpeptide levels were significantly associated and positively correlated with serum triglyceride, blood pressure, fasting plasma glucose and negatively correlated with HDL-C in the cases.Conclusion: However, this study did not find any significant association between WC (Waist Circumference) or HDL and Serum C-peptide concentration. Higher Cpeptide level was associated with the components of Metabolic Syndrome and BMI (obesity) was the most important factor affecting the C-peptide concentration to develop Metabolic Syndrome.JCMCTA 2022 ; 33 (1) : 148-153